Strategies for the retail platform to counteract match uncertainty: Virtual showroom and return or exchange policy. (February 2023) - Ma, Yong; Zhang, Cuihua; Li, Yanting
Highlights: Strategies for platforms to counteract product match uncertainty are explored. Introducing virtual showrooms can increase demands and then benefit the platform. Introducing virtual showrooms is complementary for return and exchange policies. Return policy and exchange policy are two substitutive services to each other. Managerial optimism always dominates managerial pessimism. Abstract: In a duopoly market consisting of a brick-and-motor (BM) store and a retailer platform, we explore strategies for the platform to counteract product match uncertainty. Three counteractive strategies are proposed: introducing virtual showrooms, offering a full-refund return policy and offering an exchange policy. Accordingly, duopoly competitive models are constructed to examine the roles of these strategies in mitigating product match uncertainty. In addition, the interaction among these three counteractive strategies is also explored. Results show that: these three strategies have positive effects on the platform's demands but adverse effects on BM store's. Both the full-refund return policy and the exchange policy can benefit the platform, especially the exchange policy. Nevertheless, whether introducing virtual showrooms can benefit the platform mainly relies on the establishing cost. In most cases, it is more advisable for the platform to offer an exchange policy rather than a full-refund return policy. Generally, introducing virtual showrooms and offering a return policy (an exchange policy) are two complementary methods, but the refund return policy can be seen as a replaceable measure for the exchange policy. In extensions, we explore the impacts of endogenous signal accuracy, managerial optimism and the partial-refund return policy. Several findings are also achieved: it is always beneficial to establish virtual showrooms if the platform can endogenously determine the accuracy of the information disclosed by the virtual showroom. Compared with managerial pessimism, managerial optimism generates more profits for the platform. A generous return policy leads to a higher selling price and greater profits for the platform.